Rethinking Religion: A Critical-Historical Analysis of the Western Construction and Its Non-Western Negotiations - Mohomed, Carimo (Maddah: Journal of Advanced Da'wah Management Research, 2025)
The concept of religion as it is globally understood today is a modern Western construction that is not universal. Nevertheless, it has been widely applied to non-Western cultures without adequate consideration of their historical and epistemological contexts. The singular category of “world religions” often oversimplifies highly diverse belief systems and generates epistemic bias, as seen in the labeling of Buddhism in Japan and Hinduism in India. This study aims to examine the conceptual origins of religion as a Western category, trace its application within colonial contexts, and analyze how non-Western cultures respond to the dominance of this definition. The research employs a critical qualitative approach through a historical-critical literature review and critical discourse analysis, framed by social constructionist and postcolonial theories. Japan and India are purposively selected as case studies. The findings reveal that non-Western societies are not merely passive recipients of the Western category of religion, but actively engage in resistance, adaptation, and the reconstruction of meaning based on their local contexts. This research affirms that religion is not a neutral or universal concept, but a historically and politically produced category that is continuously negotiated.